2009
DOI: 10.1086/604719
|View full text |Cite
|
Sign up to set email alerts
|

“Never Events”: Not Every Hospital‐Acquired Infection Is Preventable

Abstract: Medicare stopped reimbursing United States hospitals for several complications or comorbidities developed during hospitalizations effective 1 October 2008. The Centers for Medicare and Medicaid Services selected high-cost or high-frequency events from the National Quality Forum's list of "never events" for inclusion in this reimbursement change. Several of these complications and/or comorbidities are nosocomial infections, a significant proportion of which are not likely to be preventable. Attempts to eliminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 8 publications
1
55
0
1
Order By: Relevance
“…It is unlikely that even complete compliance with all the proposed measures will reduce the risk of HAI to zero [40] and this realism should be reflected in any future metrics or targets [41]. M a n u s c r i p t…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely that even complete compliance with all the proposed measures will reduce the risk of HAI to zero [40] and this realism should be reflected in any future metrics or targets [41]. M a n u s c r i p t…”
Section: Discussionmentioning
confidence: 99%
“…5 Next, in October 2008, CMS stopped reimbursing hospitals for a number of costly and common hospital-acquired complications, including hospital-acquired bloodstream infections and urinary tract infections, patient falls, and pressure ulcers. 3,6 VBP is the latest and most comprehensive step that CMS has taken in its decade-long effort to shift from volume to value-based compensation for inpatient care.…”
Section: Historical Context For Vbpmentioning
confidence: 99%
“…These concerns were largely related to the potential for unnecessary diagnostic testing of patients (Wald & Kramer 2007;Saint, Meddings, Calfee, Kowalski, & Krein, 2009); diversion of personnel and other resources away from general patient care and prevention leading to additional time, personnel, and resource consumption (Brown, Doloresco, & Mylotte, 2009;McHugh, Martin, Orwat, & Dyke, 2011;McHugh, Van Dyke, Osei-Anto, & Haque, 2011); and reduction or changes in health care worker staffing due to decreased reimbursement (Parish 2008;Brown et al, 2009). At least one source suggested that public disclosure of HAC rates would help patients make better-informed health care choices (McKibben et al, 2005).…”
Section: Introductionmentioning
confidence: 99%